2020
DOI: 10.1177/0885328220907775
|View full text |Cite
|
Sign up to set email alerts
|

In vitro endothelial differentiation evaluation on polycaprolactone-methoxy polyethylene glycol electrospun membrane and fabrication of multilayered small-diameter hybrid vascular graft

Abstract: During development of functional tissue engineered vascular graft, ensuring endothelialization at inner layer and mechanically strong outer layer is considered as challenging. The study objective was to fabricate a multilayered artificial blood vessel by dual syringe electrospinning technique. The presented graft was composed of polycaprolactone-methoxy polyethylene glycol which acts as an inner layer whereas Poly [4,4'-methylenebis(phenyl isocyanate)-alt-1,4butanediol/di(propylene glycol)/polycaprolactone] (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…On the other hand, the hydrophilic character improves the polarity and adhesiveness of the surface, which makes cell attachment and proliferation more possible 62 . Previous studies have reported that cells favorably attach to surfaces with an average contact angle of 60–70° 63 . Therefore, various surface modification studies are carried out in the literature to improve the wettability and cell adhesion properties of PLA‐ and PCL‐based surfaces 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hydrophilic character improves the polarity and adhesiveness of the surface, which makes cell attachment and proliferation more possible 62 . Previous studies have reported that cells favorably attach to surfaces with an average contact angle of 60–70° 63 . Therefore, various surface modification studies are carried out in the literature to improve the wettability and cell adhesion properties of PLA‐ and PCL‐based surfaces 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the inner layer of the graft, polycaprolactone-methoxy polyethylene glycol significantly improved the hydrophilicity and anti-thrombogenic properties when compared to PCL or PU-PCL membranes. Additionally, based on in vivo assessment, the polycaprolactone-methoxy polyethylene glycol membrane strengthened the differentiation of rat bone marrow stem cells into ECs and also significantly facilitated the protein and mRNA gene expression of CD31, Flk-1, and vWF, which was associated with angiogenesis [ 48 ]. Our previous study also demonstrated that Col fabricated with 43.5 ppm of Au nanoparticles significantly enhanced CD31 expression as well as promoted the endothelial differentiation for MSCs [ 25 ], which was corresponded to Figure 5 in current research.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of linkage were explored to immobilize the drug on polymer chains such as amide bond through carbodiimide, thiol-ene bonds, and metal-free click chemistry. Most of the growth factors such as transforming growth factor-β1 (TGFβ1), Bone morphogenetic protein (BMP-2) [3][4][5], Bone morphogenetic protein-7 (BMP-7) [60,61], and vascular endothelial growth factor (VEGF) [4,5,62], have been conjugated through aminecarboxylic acid reaction to form amide bonds [59].…”
Section: Covalent Conjugation Of Drug-hydrogelmentioning
confidence: 99%